Evaluation of Cotton Cultivar and At-Plant Nematicide Application on Seasonal Populations of Reniform Nematode - Whitney D. Crow (MDPI AG, 2021)
The reniform nematode, Rotylenchulus reniformis (Linford and Oliveira), remains a common, widespread nematode pest of cotton across the southern United States. Trials were conducted during 2017 at three non-irrigated locations: one location in Hamilton, MS, and two locations in Tchula, MS, in field settings with a history of cotton production and documented economically-damaging reniform nematode populations. Trials were designed to evaluate the response of two cotton cultivars to in-furrow nematicides consisting of aldicarb, 1,3-dichloropropene, and a non-treated control applied for nematode suppression. No significant interactions between cotton cultivar and nematicide were observed. However, treatment with 1,3-dichloropropene produced greater plant biomass, and plant height compared to aldicarb-treated cotton and the nontreated. Nematode densities were suppressed with the use of 1,3-dichloropropene compared to aldicarb and the non-treated control. The use of 1,3-dichloropropene resulted in positive early-season plant growth responses; however, these responses did not translate into greater yield.